The Role of Economic Factors in the Choice of Medical Providers in Rwanda - Ruhara, Charles Mulindabigwi; Mbonigaba, Josue (Journal of Economics and Behavioral Studies, 2016)
The purpose of this paper is to investigate the role of economic factors in choosing alternative service providers and to recommend suitable measures that could be taken to improve the use of health services in Rwanda. The study uses a multinomial logit framework and employs the Integrated Household Living Conditions Survey (EICV2) conducted in 2005 by the National Institute of Statistics of Rwanda (NISR). To handle the problem of endogeneity, we estimate a structural model. The results indicate that health insurance is an important factor in the choice of health facilities. User fees are major financial barriers to health care access in Rwanda. The results suggest that as household income increases, patients shift from public to private health facilities where quality is assumed to be high. A number of policy recommendations emerge from these findings. First, as insurance is an important factor in choosing a health care facility, policies that reduce health care costs to patients would substantially increase the use of health services. Second, since an increase in income allows the patient to shift to private facilities, the government should consider subsidizing private health facilities to enable access to care in private sector facilities by low-income households. Finally, since distance affects access to health care in Rwanda, there is a need to improve geographical accessibility to health facilities across regions by upgrading and expanding transportation and health infrastructures.